2018
DOI: 10.18203/2320-1770.ijrcog20180192
|View full text |Cite
|
Sign up to set email alerts
|

Correction with oral hydration improves maternal and perinatal outcome in women with third trimester isolated oligohydramnios

Abstract: Background: Oligohydramnios is related to serious maternal and fetal complications. In case of isolated oligohydramnios in third trimester maternal oral hydration has shown promising results in improving maternal and perinatal outcome. Methods: This study was conducted on 50 pregnant women complicated by idiopathic oligohydramnios (AFI<5) in third trimester. Their pre hydration daily fluid intake was noted and they were advised to take oral fluids more than their usual intake (according to their convenience). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…They observed that the differences among the subgroups were significant even at the time of birth. Results were corroborated by another study [19]. Our study, however, has not assessed different rates of fluid intake with resultant AFI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…They observed that the differences among the subgroups were significant even at the time of birth. Results were corroborated by another study [19]. Our study, however, has not assessed different rates of fluid intake with resultant AFI.…”
Section: Discussionsupporting
confidence: 84%
“…The birth weight and APGAR scores were also significantly better in the hydration group than the control group. Increase in birth weight and APGAR scores with improvement of oligohydramnios was observed in other studies as well [ 19 , 21 - 22 ]. The effect of increasing birth weight and improved fetal outcomes maybe attributed to the increased uteroplacental perfusion.…”
Section: Discussionsupporting
confidence: 76%
“…Oligohydramnios is a clinical condition when the amniotic fluid volume is <500 ml or AFI of <5 cm or <5 percentile of gestational age or a single deepest pocket of <2 cm (Chauhan et al 2018). In general, the prevalence of oligohydroamnios in pregnant women is 3−5%, and it commonly occurs in the third trimester (Aggarwal & Patra 2018). A study conducted in Rosemiarti et al…”
Section: Introductionmentioning
confidence: 99%